Desenvolvimento de microesferas mucoadesivas de claritromicina para tratamento de infecções causadas por "Helicobacter pylori" - Andrea Fialho de Souza Lima (2008)
Helicobacter pylori, a gram negative bacterium, habitats the stomach ofabout half of the world population. The infection caused by this bacterium is associated with some types of gastroduodenal inflammatory diseases that can reach the stage of an acute or chronic gastritis, gastric or duodenal ulcer and gastric cancer. Clarithromycin, a macrolide antimicrobial agent, has been adopted as a first therapy line for H. pylori infection treatment associated to the metronidazole or to the amoxicillin and a proton pump inhibitor. However there is a high rate of failure in completely infection eradication using this treatment, whichcan be related to the short permanency time and instability of the antimicrobials agents in stomach. The target of this work was to prepare clarithromycin mucoadhesive microspheres with controlled liberation in the gastric mucosa for improving its clinical efficacy for the Helicobacter pylori infection treatment. Firstly, It has been necessary to validate the method for the quantification of clarithromycin by high efficiency liquid chromatography (CLAE). In the following step, mucoadhesive microspheres with clarithromycin were been prepared using asethylcellulose as the matrix and carbopol 934P as the mucoadhesive polymer. After, these microspheres have been characterized due to their size, morphology and release profile of the clarithromycin in an artificial gastric mean with milk as an alimentary standard. At the end, an in vitro mucoadhesion study has been performed. The results have made evident that it was possible validating clarithromycin quantification method by CLAE, microspheres have presented spherical shape and size from 1 to 2 m, about 30% of the clarithromycin entrapped in the microspheres has been released after 4 hours and they suggest along time action, and besides, that microspheres adhere in vitro to the gastric mucosa. These results will be after confirmed in vivo before of proposing this new system for Helicobacter pylori treatment